2015
DOI: 10.1175/mwr-d-15-0002.1
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Wind Event on the Ross Ice Shelf, Antarctica: A Case Study of Scale Interactions

Abstract: In situ observations, satellite imagery, numerical weather prediction, and reanalysis fields are used to investigate the synoptic and mesoscale environment of a strong wind event (SWE) at McMurdo Station/Ross Island region on the Ross Ice Shelf, Antarctica, on 10 October 2003. The SWE occurred during the passage of a sequence of three mesoscale low pressure systems from the central Ross Ice Shelf to the southwest Ross Sea. A potential vorticity (PV) analysis showed that the lows drew air of continental origin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In conclusion, the effect of topography along the AP played a critical role in the occurrence of the strong wind event at KSJ on 7 January 2013, accounting for ~50% of the total wind speed. There are several previous studies that have highlighted the influence of topography on strong wind events over Antarctica (Steinhoff et al 2008, Nigro et al 2012, Orr et al 2014, Chenoli et al 2015). Whereas previous studies mainly analysed the indirect influence of topography through weather analysis, this study quantitatively evaluated the effect of the complex topography of the AP on the occurrence of a strong wind through a series of direct numerical sensitivity experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the effect of topography along the AP played a critical role in the occurrence of the strong wind event at KSJ on 7 January 2013, accounting for ~50% of the total wind speed. There are several previous studies that have highlighted the influence of topography on strong wind events over Antarctica (Steinhoff et al 2008, Nigro et al 2012, Orr et al 2014, Chenoli et al 2015). Whereas previous studies mainly analysed the indirect influence of topography through weather analysis, this study quantitatively evaluated the effect of the complex topography of the AP on the occurrence of a strong wind through a series of direct numerical sensitivity experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Nigro et al (2012) investigated a strong wind event observed at the Sabrina Automatic Weather Station (AWS) over the Ross Ice Shelf and revealed that forcing associated with the barrier wind corner jet to the north-west of the Prince Olav Mountains was the major factor in controlling the maximum wind speed. Steinhoff et al (2008) and Chenoli et al (2015) showed that downslope windstorms caused by the topography of Mina Buff and Black Island are among the factors contributing to the occurrence of strong winds at McMurdo, West Antarctica. Orr et al (2014) showed that strong wind events at Mawson, East Antarctica, were the result of the barrier jet and downslope windstorm caused by the topography around Mawson, together with a strengthening of the katabatic flow associated with the approach of a deep depression towards the coast.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies focused on the role of winds in the Antarctic coastal polynyas on seasonal or longer time scales. However, atmospheric conditions along the Antarctic coast are characterized by high-frequency wind events associated with the passages of synoptic-or mesoscale cyclones (Turner et al, 2009;Chenoli et al, 2015;Weber et al, 2016;Wang et al, 2021). The coastal margin of Antarctica is regarded as the most active cyclogenetic region on earth due to the existence of a strong baroclinic zone around the Antarctic continent (Parish and Cassano, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of barrier jet and katabatic wind produced the strong wind. Chenoli et al () investigated a strong wind event at McMurdo Station (77.9°S, 166.7°E) and the Ross Island region on the Ross Ice Shelf using in situ observations, satellite imagery, numerical weather prediction, and reanalysis data. On 10 October 2003, when wind speed of 16 m/s was observed at McMurdo Station, there were three mesoscale low‐pressure systems that passed from the central Ross Ice Shelf to the southwestern Ross Sea.…”
Section: Introductionmentioning
confidence: 99%